2009
DOI: 10.1111/j.1447-0594.2009.00533.x
|View full text |Cite
|
Sign up to set email alerts
|

Association between falls and high‐risk medication use in hospitalized Asian elderly patients

Abstract: Elderly hospitalized patients on hypnotic drugs, cough preparations and anti-platelets were more likely to fall. Appropriate usage of analgesics, especially paracetamol, to relieve pain may reduce falls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0
5

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 25 publications
0
25
0
5
Order By: Relevance
“…Fifty seven percent of the studies did not specify the medication, class or substances included in the group (only mentioned, for instance, sedative hypnotics, without indicating any specific drug) (Costa-Dias et al, 2014;Pierce Jr. et al, 2013;Obayashi et al, 2013;Lamis et al, 2012;Chang et al, 2011;Bun, Serby, Friedmann, 2011;Mamun, Lim, 2009;Tanaka et al, 2008;Angalakuditi, Gomes, Coley, 2007;Vassalo et al, 2006;Krauss et al, 2005;Vassalo et al, 2004;Aisen, Deluca, Lawlor, 1992). Some articles focused their studies on all central nervous system medications (Lamis et al, 2012) (without establishing any distinction between the pharmacological groups).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Fifty seven percent of the studies did not specify the medication, class or substances included in the group (only mentioned, for instance, sedative hypnotics, without indicating any specific drug) (Costa-Dias et al, 2014;Pierce Jr. et al, 2013;Obayashi et al, 2013;Lamis et al, 2012;Chang et al, 2011;Bun, Serby, Friedmann, 2011;Mamun, Lim, 2009;Tanaka et al, 2008;Angalakuditi, Gomes, Coley, 2007;Vassalo et al, 2006;Krauss et al, 2005;Vassalo et al, 2004;Aisen, Deluca, Lawlor, 1992). Some articles focused their studies on all central nervous system medications (Lamis et al, 2012) (without establishing any distinction between the pharmacological groups).…”
Section: Resultsmentioning
confidence: 99%
“…Seventeen studies attributed inpatient falls to anxiolytics use (Tapper, Risech-Neyman, Segupta, 2015;O'Neil et al, 2015;Mamun, Lim, 2009;Lamis et al, 2012;Frels, 2002;Dauphinot et al, 2014;Costa-Dias et al, 2014;Tanaka et al, 2008;Chang et al, 2011;Angalakuditi, Gomes, Coley, 2007;Shuto et al, 2010;Cashin, Yang, 2011;Vassalo et al, 2004;Mendelson, …”
Section: Anxiolyticsmentioning
confidence: 99%
See 1 more Smart Citation
“…En algunos casos, las caídas son la primera manifestación de una nueva enfermedad o de la pérdida de control de una enfermedad preexistente. La medicación debe ser vigilada en colaboración con el médico, ya que puede ocasionar sedación y pérdida del equilibrio que suelen generar caídas (15,(41)(42)(43)(44)(45)(46).…”
Section: Resultsunclassified
“…Results of that case-control study showed strong positive associations at 0 days for all classes of medication (β-blockers, angiotensin-converting enzyme inhibitors, calcium antagonists, thiazides). Surprisingly, only thiazides showed significant ORs of falling during elapsed times of [1][2][3][4][5][6][7][8][9][10][11][12][13][14] 16 A study showed that the current prescribing of angiotensin system-blocking medications, including angiotensin-converting enzyme inhibitors and angiotensinreceptor blockers, had a protective effect against fall risk in older people. 29 This prospective cohort study in 520 community-dwelling older people indicated that people taking angiotensin system-blocking medications were less likely to fall (OR 0.68, 95% CI 0.48-0.97; P,0.05) after adjusting for potential confounders.…”
mentioning
confidence: 99%